Benteng Jepang: Tinggalan Arkeologis Berkaitan dengan Pendudukan Jepang di Kota Medan - Jufrida Jufrida (Balai Arkeologi Sumatera Utara, 2008)
AbstractDuring the period of Japanese occupation of Medan in particular and North Sumatera in general around 1942 - 1945, resulted a fortress as an archaeological remains. Now, it becomes as the adding of Japanese historical record in Medan.